Optimizing regional development through transformative urbanization - Benna, Umar G. 1942 (Advance in electronic government, digital divide and regional developmrnt (AEGDDRD) book series, 2019)
"This book explores the emerging values and visions guiding the rise of new platforms for digital activities, crowdsourcing, crowdfunding and others that are shaping new development tools in the developing world. It also highlights how the social sector organizations apply digital technologies to increase quality of life of their members and with what effects on urban growth"-- c Provided by publisher